Orientacja rynkowa w przedsiębiorstwach przetwórstwa i handlu mięsem - Knecht, Damian (Market Orientation in Meat Processing Industry and Meat Trading Enterprises, 2006)
A study of salespeople indicates their good understanding of market orientation as well as knowledge of marketing tools and their use. The major concerns are that companies do not conduct constant market research and that only a small percentage of employees participate in trainings. Executives' indications concerning the improvement in profitability and the evaluation of the current sales organization and management system ought to be taken into account not only while planning marketing activities, but also, primarily, while organizing sales. Although a number of opportunities exists for the native sector in the EU meat market, market orientation ought to be consequently developed.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Marketing (2); 2006; nr 1110, s. 126-132